Cross–National Collaboration of Marketing Personnel within a Multinational: Leveraging Customer Participation for New Product Advantage. Issue 4 (December 2016) - Griffith, David A.; Lee, Hannah S.
Multinational success in building new product advantage through customer participation is contingent on a multinational's ability to understand the moderating influence of cross-national collaboration of its marketing personnel. The findings from a survey of global marketing managers indicate that customer participation as an information source positively influences new product advantage, but this effect is dampened when cross-national collaboration within a multinational is high. However, customer participation as a codeveloper positively influences new product advantage only when the level of cross-national collaboration is high. The contrasting moderating effects of cross-national collaboration have important implications for international marketing theory and practice.